The Impact of Cultural Intelligence and Employee Voice on Organizational Agility - El ziadi, Maha (The Arab Journal of Administration, 2023)
The study aims to determine the impact of cultural intelligence and employee voice on organizational agility, and determine the impact of the moderator variable employee voice on the relationship between cultural intelligence and organizational agility. Also, to know the significance differences of cultural intelligence, employee voice and, organizational agility as for the higher, middle, supervisional administrative levels and paternal jobs in five stars hotels in Cairo and Giza. To achieve this objective a questionnaire has been developed and distributed to a sample consists of 278 employees, of which 255 were valid for statistical analysis. The study found that there is a statistically significant effect between cultural intelligence, employee voice, and organizational agility. Also, there are significant differences between the higher, middle, supervisional administrative levels and paternal jobs as related to their perception with cultural intelligence, employee voice and, organizational agility and the result were in favor of higher and middle administrative level.